2012
DOI: 10.1136/gutjnl-2012-302514b.127
|View full text |Cite
|
Sign up to set email alerts
|

PMO-127 Biological effects of oral nanoporous carbon in bile duct ligated rats

Abstract: and bacterial challenge at baseline, and following 2 h stimulation with lipopolysaccharide (LPS) and ammonia. Pro-and anti-inflammatory cytokines were determined by CBA. Results Baseline neutrophil TLR9 expression was significantly higher in patients with HE (ALF: Grade 3/4 vs controls: p<0.02, vs grade 0e2: p<0.03) (Cirrhotics: Grade 3/4 vs controls: p<0.03, vs grade 0e2: p<0.05). Moreover their baseline TLR9 expression was associated with severity of HE and higher IL6 and IL8 levels. CD16 expression was down… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Proof-of-concept studies administering Yaq-001 to bile duct ligated rats, confirmed its impact on the removal of these molecules and results in pleiotropic beneficial effects, characterised by a reduction in the severity of endotoxaemia, liver injury, markers of systemic and hepatic inflammation, portal hypertension, renal dysfunction and severity of hepatic encephalopathy. 109 It is important to note that this effect is not associated with any antibacterial properties in vitro, but changes in the microbiome of the bile duct ligated rats was observed when administered in vivo. 110 Although the significance of these changes is not clear, the data indicated that alterations to the microenvironment, induced by Yaq-001, change the gut microbial flora.…”
Section: Adsorbentsmentioning
confidence: 98%
See 1 more Smart Citation
“…Proof-of-concept studies administering Yaq-001 to bile duct ligated rats, confirmed its impact on the removal of these molecules and results in pleiotropic beneficial effects, characterised by a reduction in the severity of endotoxaemia, liver injury, markers of systemic and hepatic inflammation, portal hypertension, renal dysfunction and severity of hepatic encephalopathy. 109 It is important to note that this effect is not associated with any antibacterial properties in vitro, but changes in the microbiome of the bile duct ligated rats was observed when administered in vivo. 110 Although the significance of these changes is not clear, the data indicated that alterations to the microenvironment, induced by Yaq-001, change the gut microbial flora.…”
Section: Adsorbentsmentioning
confidence: 98%
“…It is regulated as a device in Europe and its oral administration could reduce the trans-intestinal migration of bacterial endotoxins produced by organisms resident in the gut. 109 In vitro studies have shown that Yaq-001 preferentially removes hydrophobic substances and those with molecular weights up to approximately 70kDa. Therefore, Yaq-001 can adsorb gut-derived toxins such as ammonia, asymmetric dimethylarginine, acetaldehyde, hydrophobic BA, cytokines such as TNF alpha and interleukin-6, as well as bacteria derived products like LPS and exotoxins (Fig.…”
Section: Adsorbentsmentioning
confidence: 99%
“…Indeed, cation-exchange resin targeting hyperkalemia and hyperphosphatemia has shown efficacy [ 160 ]. Nonabsorbable nanopore carbon reduced portal vein pressure and liver biochemical markers in rats that underwent bile duct ligation, resulting in decreased endotoxin-induced KC stimulation [ 161 , 162 ]. Therefore, by targeting the gut–liver axis, adsorbent materials is a possible treatment strategy for sepsis.…”
Section: Therapymentioning
confidence: 99%